1904
DOI: 10.1002/cber.190403701141
|View full text |Cite
|
Sign up to set email alerts
|

Ueber eine neue Darstellungsweise von Phenyläthersalicylsäure

Abstract: Losung mit Petrolather, 158-159" schmelzen. 0.1 167 g Sbst. : 0.2.509 g N (210, 725.4 mm). Cs Hi7 NS 0. wobei es in Nadeln erhalten wird, die bei GO,, 0.1007 g H10. -0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(94 citation statements)
references
References 1 publication
1
92
0
1
Order By: Relevance
“…Gaunt recently showed that treatment of anilides with catalytic Cu(OTf) 2 and Ph 2 IOTf resulted in meta-arylation of acetanilide.…”
Section: -150mentioning
confidence: 99%
“…Gaunt recently showed that treatment of anilides with catalytic Cu(OTf) 2 and Ph 2 IOTf resulted in meta-arylation of acetanilide.…”
Section: -150mentioning
confidence: 99%
“…Modern Ullmann coupling reactions [1][2][3][4] (Scheme-I) are widely used in organic synthesis and C-hetero atom bond formation [5]. These reactions are essential tool in modern laboratories and industries for the synthesis of bio-active drugs, agro-chemicals and polymers [5,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The classical Ullmann reaction for diaryl ether synthesis often requires extremely harsh reaction conditions, i.e. high temperatures (200-300 o C), strong polar and toxic solvents and the use of stoichiometric quantities of copper, and generally gives low yields [10], so a number of other methodologies for the synthesis of diaryl ethers have been developed in recent years [11]. Meanwhile, the fact that the strategic use of protective groups is a necessary and time-consuming tactic in organic synthesis is well-known, so a merging of protective group chemistry with other transformations that can shorten a reaction sequence and improve synthetic efficiency and convenience is always of great interest.…”
Section: Introductionmentioning
confidence: 99%